2011
DOI: 10.1002/pri.524
|View full text |Cite
|
Sign up to set email alerts
|

Pain Impacts on Quality of Life and Interferes with Treatment in Adults with Cystic Fibrosis

Abstract: Pain is common in adults with CF, irrespective of clinical status, and may interfere with important physiotherapy treatments. Although pain intensity is generally mild, those with a negative emotional response to pain have significantly impaired HRQOL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
43
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 43 publications
0
43
1
Order By: Relevance
“…In a previous study, female sex was associated with higher scores in body image and weight scales, and females reported lower physical functioning and vitality scores. 39 However, Shoff et al 40 found no significant sex differences in mean CFQ dimension scores or nutritional status scores in children and adolescents, but the strength of association between nutritional status and CFQ scores differed between boys and girls for some dimensions, such as physical functioning. In the present study, the 6MWD was an independent predictor for both WHOQOL-BREF and CFQOL scores.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In a previous study, female sex was associated with higher scores in body image and weight scales, and females reported lower physical functioning and vitality scores. 39 However, Shoff et al 40 found no significant sex differences in mean CFQ dimension scores or nutritional status scores in children and adolescents, but the strength of association between nutritional status and CFQ scores differed between boys and girls for some dimensions, such as physical functioning. In the present study, the 6MWD was an independent predictor for both WHOQOL-BREF and CFQOL scores.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies showed that pulmonary function in adults with CF is also a significant predictor of CFQOL scores. 38,39 In a longitudinal study, Abbott et al 38 observed that the percent-of-predicted FEV 1 significantly correlated with all domains except body image. In contrast, in the present study, the percent-of-predicted FEV 1 showed an association only with the social relationship domain in the WHOQOL-BREF questionnaire and the respiratory symptom domain in the CFQOL questionnaire.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, greater attention is being paid to patients’ quality of life (QOL). CF patients frequently complain of pain, mainly back pain, chest pain and headache [4][11]. Although pain in adults with CF is associated with lower QOL [5][6], [11], increased risk of exacerbation [6] and decreased survival [6], [12], it is often neglected by the treating physicians [5], [8].…”
Section: Introductionmentioning
confidence: 99%
“…CF patients frequently complain of pain, mainly back pain, chest pain and headache [4][11]. Although pain in adults with CF is associated with lower QOL [5][6], [11], increased risk of exacerbation [6] and decreased survival [6], [12], it is often neglected by the treating physicians [5], [8]. In addition to drug treatment, many patients with CF use non-drug treatments and complementary and alternative medicine (CAM) [5][6], [8], [13][15] including osteopathic manipulative treatment (OMT).…”
Section: Introductionmentioning
confidence: 99%
“…Advances in the treatment have improved the life expectancy of people with CF [2]. The increased longevity of adults with CF is accompanied by a rising prevalence of secondary complications including pain [3], which can be associated with the diagnosis and treatment of the disease, and the disease itself [4].…”
mentioning
confidence: 99%